Beauty From the Waist Up: Twitch Drag, Digital Labor, and Queer Mediated Liveness. (July 2022) - Persaud, Christopher J.; Perks, Matthew E.
Game live streaming scholarship has explored how the medium offers diverse forms of self-presentation, increasingly commercialized avenues of promotion, and vivid examples of participatory cultural production. This article focuses on the vibrant Twitch.tv subculture of drag artist game live streamers (or drag streamers) who engage in digital labor and performance, offer a distinct case of queer internet microcelebrity, and highlight tensions concerning the representation of queer identities in the social media age. As more queer people begin developing branded social media selves in spaces of real-time performance, such as the increasing number of drag streamers on Twitch, we contend that their performance of queerness becomes tied up in both potential avenues for monetization and the expectations of their followers. We conclude by developing the concept of "queer mediated liveness" to describe the labor, esthetics, and live content creation of queer streamers.